2003
DOI: 10.1089/108729103322555980
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis and HIV Prevalence among Commercial Sex Workers in Central Java, Indonesia: Risk-Taking Behavior and Attitudes that May Potentiate a Wider Epidemic

Abstract: A cross-sectional study was conducted on 200 commercial sex workers (CSWs) from two brothel communities in Central Java, Indonesia, to determine the seroprevalence of syphilis and HIV and characterize associated knowledge, beliefs, and risk-taking behaviors. A questionnaire was administered and blood drawn for HIV and syphilis serologies. Focus groups with a total of 20 women were also conducted at both communities to supplement survey data. The mean CSW age was 27.3 years; mean number of clients seen per day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This is in agreement with earlier reports from Indonesia5 21 and efforts continue to strengthen the condom promotion programme. Although consistent condom use will contribute to the prevention of syphilis transmission, it will take time to establish efficient and effective programmes.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with earlier reports from Indonesia5 21 and efforts continue to strengthen the condom promotion programme. Although consistent condom use will contribute to the prevention of syphilis transmission, it will take time to establish efficient and effective programmes.…”
Section: Discussionsupporting
confidence: 93%
“…Longer truck driving careers and trips were significantly associated with HIV infection (Manjunath et al, 2002). Studies conducted in Thailand, Bangladesh, Indonesia, Nigeria and Florida (USA) indicate that condom use among truck drivers is low and/or inconsistent (Gibney et al, 2003;Morris et al, 1996;Stratford et al, 2000;Sugihantono et al, 2003;Sunmola, 2005). A study of HIV-positive truckers in Bangladesh found that over one third did not change their sexual behavior after learning that they were HIV-positive (Gibney et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with common beliefs, accumulating data support the contention that CSWs are contributing to the spread of HIV to heterosexuals (Reed, Ford, & Wirawan, 2001). As such, a burgeoning literature in this area has emerged regarding risk and protective factors for STI/HIV transmission (Sugihantono et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with common beliefs, accumulating data support the contention that CSWs are contributing to the spread of HIV to heterosexuals (Reed, Ford, & Wirawan, 2001). As such, a burgeoning literature in this area has emerged regarding risk and protective factors for STI/HIV transmission (Sugihantono et al, 2003).Established individual-level informational and attitudinal correlates of high risk behavior have been the focus of HIV prevention interventions. However, economic, organizational, legal and other macro-level structural factors have been increasingly emphasized in preventing HIV (Liu & So, 1996;Sumartojo, 2000).…”
mentioning
confidence: 99%